Strategi Pembangunan Ekonomi Pedesaan di Daerah Tertinggal Melalui Optimalisasi Potensi Lokal, Infrastruktur Pertanian, dan Teknologi Tepat Guna - Putri Amirah Hajarani; Imsar Imsar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Rural economic development in underdeveloped areas requires a strategic approach that integrates local potential, agricultural infrastructure, and appropriate technology (AT) to foster inclusive and sustainable growth. This study aims to analyze rural economic development strategies through a literature review and thematic synthesis of relevant studies. The findings reveal that optimizing local potential, such as natural and socio-cultural village resources, can enhance community economic self-reliance. Strengthening agricultural infrastructure, especially the construction of farm roads, significantly improves distribution efficiency and farmer income. The application of appropriate technology in agriculture, small enterprises, education, and healthcare further accelerates economic and social transformation in rural areas. Nevertheless, challenges such as limited basic infrastructure, digital gaps, and low technological literacy require collaborative solutions. Therefore, development strategies based on local potential, functional infrastructure, and technological innovation are essential to building independent, productive, and competitive rural communities.